Mandibular implant-retained overdenture with magnets in total edentulous patients (case report) - Machmud, Edy; Arpa, Sitti (Hasanuddin University, 2019)
Objective: According to the manufacture, fewer than 1 in 10 capsule associated with overdentures on natural teeth separated from the denture base during an 8-year clinical trial; more interestingly, none experience loss of magnetic attraction.Methods: A 50 year old female patient came to Dental Hospital Makassar Hasanuddin University wanted to fix a loose denture, which has been used for 9 years. Chief complaint was a mobile mandibular denture. Treatment for the restoration of oral function, including mastication, using mandibular implant-retained overdenture with magnets in total edentulous. Implant supported retained with magnetic attachment constitute an accurate and predictable treatment option and achieve a higher patients satisfaction.Results: The surface of both magnet and attachment keeper were coated with titanium nitride (TiN). Self-curing resin was used for luting betweenÂ magnets and denture base resin.Conclusion: Magnetic attachments can be used to retain mandibular implant overdenture.Key words: Implant supported overdenture with magnets, resorbed alveolar ridge, total edentulous